Narrative Text to Encourage Students Skill in Speaking - Duendi Sata, Nashih Rojabi; Desy Wardani, Ika; Sabartono, Ribut (Linguapedia, 2023)
This research delves into the exploration of enhancing English as a Foreign Language (EFL) students' confidence in speaking through the use of narrative text, specifically employing the movie "Up" within an Indonesian private university context. The primary research problem is framed as "How can students' speaking experience be influenced by the 'Up' movie in narrative text?" The study aims to understand the impact of using "Up" movie on students' speaking abilities in a narrative context. A qualitative research approach was employed for data collection, utilizing interviews as the primary method. The qualitative data analysis involved four key steps: Coding, Data Reduction, Data Presentation or Display, and Drawing Conclusions.